Oestrogen receptors in colorectal carcinoma. - Dawson, P M (1990)
The oestrogen receptor content of colorectal adenocarcinoma was investigated using an established ligand binding biochemical assay and two more recently introduced techniques using specific monoclonal antibodies (Abbott ER-EIA and ER-ICA assay kits). Twenty nine tumours were investigated by the ligand binding assay. Only one (3.4%) tumour gave a weakly positive result (11 fmol/mg cytosol protein); the rest were all negative. Where sufficient tissue was available, the receptors were also determined by a quantitative immunoassay in 18 patients and an immunohistochemical method in 13 patients. The results were similarly all negative. It is concluded that most colorectal carcinomas, irrespective of sex, are oestrogen receptor negative, and it is thus unlikely that hormonal manipulation would have an influence on the course of the disease.